The role of philosophical thinking in the development of natural-scientific knowledge in the 18th century - Pardayev Sultanmurad (Zien Journals, 2023)
In this article deals with the status of natural-scientific knowledge developed along with technical sciences in the non-classical landscape of the world, and at the same time the differences between them are revealed. Also, theories such as uniformism, transformism, Lamarckism, and catastrophism were analyzed as a unique status of natural-scientific knowledge. In addition, the impact of the natural-scientific knowledge formed in this period on the way of thinking of the people of the next period is revealed
Keywords: mechanical landscape; uniformism; transformism